2003
DOI: 10.1074/jbc.m302234200
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization of Transcriptional Intermediary Factor 1 Regulators and Interaction with ZNF74 Nuclear Matrix Protein Revealed by Bioluminescence Resonance Energy Transfer in Living Cells

Abstract: Transcriptional intermediary factor 1 (TIF1) ␣ and KAP-1/TIF1␤, two members of the TIF1 family of nuclear cofactors, are ubiquitous co-regulators of nuclear receptors and KRAB motif-containing zinc finger transcription factors, respectively. Despite the functional evidence suggesting a role for TIF1 proteins as modulators of transcription, the study of their interactions with transcriptional machineries in physiologically relevant systems has been difficult. Here, we have developed a bioluminescence resonance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 36 publications
1
49
0
Order By: Relevance
“…Evidence for TIF1␦ Self-association-Because of the previous demonstration that TIF1s (␣, -␤, and -␥) can form homodimers (12,37) as well heterodimers (TIF1␣-TIF1␥) (12), we examined the dimerization capacities of TIF1␦ using the yeast two-hybrid system. In this assay, DBD-TIF1␦ was coexpressed with AAD fusion proteins between the AAD of VP16 and any one of the family members (AAD-TIF1␣, AAD-TIF1␤, AAD-TIF1␥, and AAD-TIF1␦; Fig.…”
Section: Tif1␦ Associates Preferentially With Hp1␥ and Forms Multiplementioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for TIF1␦ Self-association-Because of the previous demonstration that TIF1s (␣, -␤, and -␥) can form homodimers (12,37) as well heterodimers (TIF1␣-TIF1␥) (12), we examined the dimerization capacities of TIF1␦ using the yeast two-hybrid system. In this assay, DBD-TIF1␦ was coexpressed with AAD fusion proteins between the AAD of VP16 and any one of the family members (AAD-TIF1␣, AAD-TIF1␤, AAD-TIF1␥, and AAD-TIF1␦; Fig.…”
Section: Tif1␦ Associates Preferentially With Hp1␥ and Forms Multiplementioning
confidence: 99%
“…Amino acid comparison revealed that, among the three mammalian members of the family, TIF1␥ is closer to TIF1␣ than to TIF1␤ (50% overall identity between TIF1␣ and TIF1␥ and ϳ30% identity among the other TIF1s) (9,36). In vitro, TIF1␣ and TIF1␥ hetero-oligomerize as efficiently as they homo-oligomerize, whereas TIF1␤ does homooligomerize but does not hetero-oligomerize with TIF1␣ or TIF1␥ (12,37). Moreover, it has been shown that an overexpression of TIF1␥ in transiently transfected cells can interfere with the transrepression activity of TIF1␣ (12).…”
mentioning
confidence: 99%
“…Currently, assays to identify and characterize these interactions are primarily in vitro binding assays (4)(5)(6). In the past 5 years, imaging strategies based on yeast two-hybrid assays, reporter complementation assays, and resonance energy transferbased assay methods (7)(8)(9)(10)(11)(12) have been developed. However, all of these approaches have encountered shortcomings, limiting their potential to serve as a single imaging assay for measuring proteinprotein interactions from both single cells and physiologically relevant small living animal models.…”
Section: Introductionmentioning
confidence: 99%
“…All TIF1 family members (TIF1␣, ␤, ␥, ␦, and bonus) are characterized by an N-terminal tri-partite motif (named TRIM or RBCC) composed of a RING (really interesting new genes) finger followed by two B-boxes and a coiled-coil domain as well as a C-terminal bi-partite motif encompassing a PHD (Plant HomeoDomain) finger and a bromo domain (2, 8 -11). The RBCC motif of TIF1␤ is known to homodimerize and to specifically interact with the KRAB domain of KRAB multifinger proteins (12)(13)(14). The TIF1␤ PHD finger and bromo domain were reported to cooperate in transcriptional repression via recruitment of repressive enzymatic activities such as histone deacetylase complexes (NurD/Mi2-␣) and a methyltransferase protein (SETDB1) (15,16).…”
mentioning
confidence: 99%